“Vida simples, pensamento elevado”: as experiências comunitárias de Lothlorien (BA) e Nova Gokula (SP) entre 1978–2000 - Lopes, Regiane Luzia (2022)
In this study, we make a deeper analysis of the community experiences of Lothlorien – Centro de Cura e Crescimento (Caeté-Açu/BA) and Nova Gokula (Pindamonhangaba/SP) from 1978 to 2000. Located in different regions of Brazil and designed from different perspectives, without subsequent relations with each other, these two community experiences urged us to know whether it was possible to establish a comparative analysis between them. Thus, starting with the assumption that these communities were, in a way, interconnected by remaining elements of the counterculture from the 1960s, we started to discover the intersection links that brought them together and the aspects that distanced them, With that, we remarked their peculiarities and expanded our reflection on these experiences as sociocultural interventions that attribute political, nonpartisan meaning to daily life. From the very beginning, this research considered the utopian potential and the principles that guided these community projects, decoded in social strategies and practices developed by them, not only marked by creativity and boldness, but also by contradictions and limits in transposing an ideal to the concreteness of the real. The reflection that these experiences offer us as alternatives in the way of being and living socially and the meanings inferred by them, irrevocably, widen our views on social relations, the politicalization of everyday life and the construction of memories